From the sub-prefect Teodomiro Gutiérrez to the revolutionary Rumi Maqui Ccori Zoncco (stone hand, golden heart). Letters to Andres A. Caceres - Gonzales Alvarado, Osmar (2020)
A trail of mystery has remained about Teodomiro Gutiérrez. He was a military man who sympathetic to the claims leading a rebellion. Some suppose that he died in some confrontation against the forces of order; others that after the conflict disappeared without a trace but material for the legend. In this article the author tries to elucidate some these questions on the basis of unpublished letter from the Andrés A. Cáceres of the National Library of Peru.